A Modified Lysimeter Study for Phyto-Treatment of Moderately Saline Wastewater Using Plant-Derived Filter Bedding Materials - Marathe, Deepak; Raghunathan, Karthik; Singh, Anshika; Thawale, Prashant; Kumari, Kanchan (Frontiers in Microbiology, 2021)
The present study focuses on determining the phyto-treatment efficiency for treatment of moderately saline wastewater using organic raw materials, such as rice husk, coconut husk, rice straw, and charcoal. The moderately saline wastewater with total dissolved solids (TDS) concentration up to 6143.33 ± 5.77 mg/L was applied to the lysimeters at the rate of 200 m3 ha–1 day–1 in five different lysimeter treatments planted with Eucalyptus camaldulensis (T1, T2, T3, T4, and T5). T1 was a control without any filter bedding material, whereas rice straw, rice husk, coconut husk, and charcoal were used as filter bedding materials in the T2, T3, T4, and T5 treatment systems, respectively. Each treatment showed significant treatment efficiency wherein T3 had the highest removal efficiency of 76.21% followed by T4 (67.57%), T5 (65.18%), T2 (46.46%), and T1 (45.5%). T3 and T4 also showed higher salt accumulation, such as sodium (Na) and potassium (K). Further, the pollution load in terms of TDS and chemical and biological oxygen demand significantly reduced from leachate in the T3 and T4 treatments in comparison with other treatments. Parameters of the soil, such as electrical conductivity, exchangeable sodium percentage, and cation exchange capacity did not show values corresponding to high salinity or sodic soils, and therefore, no adverse impact on soil was observed in the present study. Also, Eucalyptus camaldulensis plant species showed good response to wastewater treatment in terms of growth parameters, such as root/shoot weight and nitrogen, phosphorus, and potassium (NPK) uptake, plant height, biomass, and chlorophyll content. Root and shoot dry weight were in the order T3 (51.2 and 44.6 g)>T4 (49.3 and 43.5 g) > T5 (47.6 and 40.5 g) > T2 (46.9 and 38.2 g) > T1 (45.6 and 37.1 g). Likewise, the total chlorophyll content was highest in T3 (12.6 μg/g) followed by T4 (12.3 μg/g), T5 (11.9 μg/g), T2 (11.5 μg/g), and the control, that is, T1 (11.0 μg/g). However, the most promising results were obtained for T3 and T4 treatments in comparison with the control (T1), which implies that, among all organic raw materials, coconut and rice husks showed the highest potential for salt accumulation and thereby wastewater treatment. Conclusively, the findings of the study suggest that organic raw material–based amendments are useful in managing the high salts levels in both plants and leachates.